PELATIHAN PEMBUATAN DAN PERHITUNGAN HARGA POKOK PRODUKSI KRIPIK PISANG KALURAHAN TRIDADI, YOGYAKARTA - Martinus Budiantara; Ratri Paramitalaksmi; Rochmad Bayu Utomo; Putri Nurmalasari; Stefanus, Carlos Deo (Bajang Institute, 2023)
In order to improve the economy of Kalurahan Tridadi through the processing of agricultural products, in other words, from bananas to banana chips. The development of banana fruit through processing into banana chips is expected to increase household income for residents, improve employment and business opportunities in rural areas, increase added value, and improve the quality of banana products. Of course, it is balanced with the ability to calculate the cost of goods produced. The purpose of implementing this PkM is to help mothers in Kalurahan Tridadi to continue to work in developing processed banana fruits, such as (1) increasing the ability to process bananas into banana chips (2) increasing the ability in packaging (3) knowing the acquisition price of making banana chips (4) connecting this banana chips business to Kedung Aren Tourism Village as a superior product. The method used is counseling and training involving 15 participants. As a result of the activity, they deepened their understanding of how to make banana chips correctly.Currently, partners also have a clear organizational structure, there is an increase in skills in making banana chips and service partners already have their own production tools and the availability of capital.